A Critical Review of Street Lighting, Crime and Fear of Crime in the British City - Cozens, Paul; Neale, R.; Whitaker, J.; Hillier, D.; Graham, M. (2003)
The UK government has recently made £300 million available to help local authorities to modernise their street lighting. In consideration of such future funding, this paper reviews the relationship between lighting and crime, explores the current theoretical explanations, and discusses the limitations of the existing BS 5489 lighting standards as they relate to crime reduction. British street lighting standards rely largely on official recorded crime statistics as the preferred measure of crime and, crucially, fear of crime maps have been shown to differ markedly from the reality suggested by recorded crime statistics (Brantingham et al, 1977; Vrij and Winkel,1991). The implications of utilising the current classification of streets according to levels of recorded crime and levels of pedestrian and traffic flows to determine acceptable lighting levels are presented. In the light of recent research on crime and street lighting, local authorities might usefully critically review lighting levels following the Crime and Disorder Act 1998. Acknowledging the emergence of the 24-hour city, the policy implications for improving the crime reduction potential of street lighting are discussed.